Post-intervention outcomes in farmer behaviour and crop diversification in Dinajpur, Bangladesh - Nandi, Ravi; Hossain, Md. Khaled; Anupama Islam Nisho; Md. Arifur Rahaman; Sumona Shahrin; Alanuzzaman Kurishi, A.S.M.; Md Saiful Islam; Mustafa Kamrul Hasan; Krupnik, Timothy J. (TAFSSA, 2024)
Crop production is highly rice-centric in Bangladesh and, although economically rational, is risky and arguably unsustainable (1). Crop diversification emerged as an important strategy for achieving sustainable agriculture in Bangladesh (2). On-farm trials were conducted to evaluate new cropping patterns in the Dinajpur district and promote crop diversification among smallholder farmers. This brief summarizes the results from post-intervention outcomes in farmer behavior covering a) preferred cropping patterns among farmers; b) perceived benefits, challenges, and transaction costs of crop diversification, and c) market awareness among trial farmers. Data were collected through face-to-face surveys involving on-farm trail farmers in the Dinajpur district.